Algunas consideraciones sobre el tribunal y el recurso de casación civil francés = A few considerations regarding the French Court of Cassation and the civil appeal in cassation - Hualde López, Ibon (CUADERNOS DE DERECHO TRANSNACIONAL, 2017)
Resumen: El presente trabajo tiene por objeto analizar, por un lado, el Tribunal de casación (Cour de cassation) de Francia, que es el órgano situado en la cúspide de la organización judicial de este país, por encima de los tribunales de primera instancia y de los tribunales de apelación. Así, se explica la estructura del tribunal casacional, que tiene seis salas de carácter permanente, divididas en secciones, y ciertas salas «especiales»; y la composición de dicho órgano jurisdiccional, con alusión a los magistrados que lo integran y al resto de funcionarios que hacen posible su correcto funcionamiento. Y, por otro lado, el recurso de casación (pourvois en cassation), haciéndose referencia a su origen y evolución, así como a los criterios que determinan su admisión. Finalmente, se da cuenta del reciente informe provisional (rapport d’étape) presentado, a instancias del primer presidente del Tribunal de casación (premier président de la Cour de cassation), por la comisión de reflexión (commission de réflexion) encargada de conducir el estudio prospectivo relativo a la reforma de este órgano jurisdiccional; y de los debates y críticas procedentes de los distintos sectores de la comunidad jurídica francesa. Palabras clave: Tribunal de casación, salas y secciones, magistrados, recurso de casación, criterios de admisión, proyecto de reforma. Abstract: This paper aims at analyzing, on the one hand, the Court of Cassation (Cour de cassation) of France, which is the organ located at the apex of the national judicial system, above the courts of first instance and the courts of appeal. Thus, it details the structure of the Court of Cassation, comprised of six permanent chambers, which are divided into sections, as well as certain «special» chambers. It also explains the composition of the Court, as regards the justices who serve on it, in addition to other officers who make possible its proper functioning. On the other hand, the article deals with the «appeal in cassation» (pourvois en cassation), with reference to its origin and evolution, as well as the criteria applied when deciding whether or not to grant review. Finally, the paper gives notice of the recent interim report (rapport d’étape) submitted, at the request of the first president of the Court of Cassation (premier président de la Cour de cassation), by the reform commission (commission de réflexion) tasked with conducting the prospective study concerning the reform of this court. The article additionally provides an overview of the related debates and criticisms coming from various sectors of the French legal community. Keywords: Court of Cassation, chambers and sections, justices, appeal in cassation, admission criteria, draft reform. doi: https://doi.org/10.20318/cdt.2017.3618